Biological & Immunological Effect of Ozonated Water on Certain Skin Pathogenic Bacteria In vivo - Baghdad Science Journal (مجلة بغداد للعلوم, 2009)
This in vivo study was conducted to investigate the effect of different concentrations of ozonated water on experimentally skin infection with some of bacterial isolates (Pseudomonas aeruginosa and Staphylococcus aureus ) which Showed dermal infection in experimental animals after 48 hours of exposure to these Microorganisms. Results revealed that ozone has the power to accelerated the healing process depending on the perfect concentration of ozonated water used and the severity of infection & nature of causative agent , in which the recovering period was 7 days for the infection caused by P. aeruginosa and 5 day for S.aureus by using the concentration 60 µg/ml . Results also indicated in this study the stimulated effect of Ozonated water on the immune system For the healthy mice at the concentration 20µg/ml through increasing in Phagocytic index ,Arthus and Delayed Type- Hypersensitivity reaction in addition to the inhibited effect of this material on this immunological Markers when the animals treated with Ozonated water at the concentration 60µg/ml . Different respond appear with the immune system For injured and infected mice when treated with ozonated water depending on the Kind of causing agent and the severity of infection .